Effects of light intensity, temperature, and circadian clock on the nyctinastic movement of Oxalis triangularis 'Purpurea' - Le You; Wanli Tuo; Zhongwu Dai; Hui Wang; Sagheer Ahmad; Donghui Peng; Shasha Wu (Technology in Horticulture)
Oxalis triangularis 'Purpurea' exhibits nyctinastic movement. While the regulation of nyctinastic movement is influenced by many factors, like light, temperature, and circadian clock, there is lack of systematic research on these factors in Oxalis L. In this study, the nyctinastic motion of O. triangularis ‘Purpurea’ leaves and flowers was recorded in a growth chamber with controlled temperature and light, and. the time and angle of opening and closing of the leaves and flowers were analyzed. The results showed that the leaves could fully expand under 8.34 μmol·m−2·s−1 light intensity in the morning and 32.20 μmol·m−2·s−1 light intensity at night, taking about 150 min for the whole process. The stronger the light intensity, the lesser time it took for the leaves to fully expand after closing. However, the light intensity had no significant effect on flower movement. As the temperature increased within the range of 15−35 °C, the leaves closed quickly, and the flowers opened rapidly. Moreover, under constant darkness, the leaves still exhibited rhythmic movement, expanding about 30° possibly due to the circadian clock, lasting for approximately 26−28 h. However, the flowers remained closed and did not open. Therefore, circadian clock does not play a significant role in the nyctinastic movement of flowers. Leaf movement is influenced by light, temperature, and the circadian clock, whereas floral movement was mainly affected by temperature. This study shed new light on the regulation of nyctinastic movement and will promote better use of O. triangularis 'Purpurea' in gardens.